2022
DOI: 10.3389/fcimb.2022.861677
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Associated Biofilm Regulation Leads to Vibrio cholerae Resistance Against Intestinal Environmental Stress

Abstract: The commensal microbes of the gut microbiota make important contributions to host defense against gastrointestinal pathogens, including Vibrio cholerae, the etiologic agent of cholera. As interindividual microbiota variation drives individual differences in infection susceptibility, we examined both host and V. cholerae gene expression during infection of suckling mice transplanted with different model human commensal communities, including an infection-susceptible configuration representing communities damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The pellets thus obtained were washed twice with 1× phosphate-buffered saline, and the bacterial suspension was adjusted to OD 600 = 0.5 and then diluted 100 times to a concentration of 1 × 10 7 CFU per ml. Each suckling mouse received 50 μl (~5 × 10 5 CFU) of cell suspensions via gavage, with the same volume of 1× phosphate-buffered saline serving as a baseline control ( Sarkar et al, 2018 ; Wang et al, 2018 ; Cho et al, 2022 ). The inoculation dose was determined through several pre-experimental explorations, and we found that higher concentration including 5 × 10 7 CFU per 50 μl and 5 × 10 6 CFU per 50 μl of bacterial suspension resulted in massive death of the suckling mice in 18 h, while 5 × 10 5 CFU per 50 μl did not.…”
Section: Methodsmentioning
confidence: 99%
“…The pellets thus obtained were washed twice with 1× phosphate-buffered saline, and the bacterial suspension was adjusted to OD 600 = 0.5 and then diluted 100 times to a concentration of 1 × 10 7 CFU per ml. Each suckling mouse received 50 μl (~5 × 10 5 CFU) of cell suspensions via gavage, with the same volume of 1× phosphate-buffered saline serving as a baseline control ( Sarkar et al, 2018 ; Wang et al, 2018 ; Cho et al, 2022 ). The inoculation dose was determined through several pre-experimental explorations, and we found that higher concentration including 5 × 10 7 CFU per 50 μl and 5 × 10 6 CFU per 50 μl of bacterial suspension resulted in massive death of the suckling mice in 18 h, while 5 × 10 5 CFU per 50 μl did not.…”
Section: Methodsmentioning
confidence: 99%